Legal Position of Notary Deed that Does Not Meet the Elements of the Agreement in the Conception of Legal Certainty - Nau, Yonatan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to determine and analyze the legal position of a notary deed that does not fulfill the elements of the agreement in the conception of legal certainty through the study of the Cooperation Agreement Deed No. 86 dated 28 June 2008 made by Notary Yoshephina Vestha Raya, SH. normative juridical with analytical descriptive research specifications. The type of data used is secondary data consisting of primary, secondary and tertiary legal materials, namely legislation, jurisprudence and court decisions that have permanent legal force, books, journals and expert opinions, as well as dictionaries or encyclopedias. All data was collected through a literature study, where the data collected was analyzed using qualitative analysis. The results of the study show that: First, a deed that has united two legal actions that have different characters and elements, namely on the one hand there is cooperation in the management of mining land (Innominaat agreement) but on the other hand there is a transfer of material rights that must be made in the form of a Nominaat agreement thus contradicting the elements of the Nominaat agreement. Such agreement deed is a violation of statutory provisions or contrary to the legality of the four terms of an agreement as stipulated in Article 1335 of the Civil Code, 1337 of the Civil Code, which relates to Article 1338 of the Civil Code and Article 1339 of the Civil Code and violates the principle of